Alteration trends and geochemical source region characteristics preserved in the fluviolacustrine sedimentary record of Gale crater, Mars. (1st February 2019) - Bedford, C.C.; Bridges, J.C.; Schwenzer, S.P.; Wiens, R.C.; Rampe, E.B.; Frydenvang, J.; Gasda, P.J.
Abstract: The Mars Science Laboratory's Chemistry and Camera (ChemCam) instrument suite on-board the Curiosity rover has analysed ∼1200 sedimentary targets during the mission up to sol 1482. These targets have included sedimentary rock, diagenetic features (e.g., fracture-associated alteration halos, mineral veins, nodules, and erosion resistant raised ridges), active aeolian fines, soils and float. We have isolated ChemCam geochemical trends relating to diagenetic features and alteration products from those of the sedimentary rock in order to identify the compositional characteristics of Gale crater's sediment source regions. The effects of grain size variation on sedimentary unit geochemistry have been taken into account by grouping and analysing geological units according to grain size. With obvious diagenetic features removed from the database, and predominately isochemical aqueous alteration inferred for the Mt Sharp Group samples, we propose that source region composition is a stronger source of geochemical change between the Bradbury and Mt Sharp Groups than open-system alteration. Additionally, a lack of correlation between the Chemical Index of Alteration (CIA) values and SiO2, MgO or FeOT indicates that the slight increase in chemical weathering of the Mt Sharp Group sediments was insufficient to overprint sediment source compositional signatures. This has led to the identification of five unique igneous endmember compositions which we hypothesise to have contributed to Gale crater's stratigraphic record. These endmembers are: (1) a subalkaline basalt, compositionally similar to the tholeiitic Adirondack Class basalts of Gusev crater, and dominant within the finer grained units up to the base of Mt Sharp; (2) a trachybasalt, mostly identified within conglomerate units from the Darwin waypoint to the base of Mt Sharp; (3) a potassium-rich volcanic source, determined from strong potassium enrichment and a high abundance of sanidine that is most dominant in the fluvial sandstones and conglomerates of the Kimberley formation; (4) a highly evolved, silica-rich igneous source that correlates with the presence of tridymite, and is recorded in the lacustrine mudstone of Mt Sharp's Marias Pass locality; and, (5) a fractionated, relatively SiO2 -rich subalkaline basalt, seen to have influenced the composition of mudstone deposited in the lower part of the Mt Sharp Group. Endmembers (1), (2), (3), and (4) have previously been identified at specific waypoints along the rover's traverse, but we show that their influence extends throughout Gale's stratigraphic record. The occurrence of detected endmembers is also strongly correlated with stratigraphic position, which suggests changing sediment source regions with time. We conclude that Gale sediment provenances were much more varied than suggested by the largely homogenous, globally-distributed Martian basalt inferred from orbit, showing that complex magmatic assemblages exist within the ancient highland crust surrounding Gale.